Relation Between Pain, Disability and Depression in Patients with Knee Osteoarthritis - Nuri Çetin,; Pınar Öztop,; Meral Bayramoğlu,; Sacide Nur Saraçgil Coşar,; Gamze Özçürümez, (Archives of Rheumatology, 2009)
Objective: The aim of this study was to investigate the relationship between pain, disability and depression in patients with knee osteoarthritis. We also aimed to examine the effects of depression treatment on pain and disability among patients with comorbid knee osteoarthritis and depression. Material and Methods: Fifty-six patients who fulfilled the American College of Rheumatology (ACR) clinical criteria for knee osteoarthritis were included in this study. A 10 cm visual analog scale was used to assess pain severity. Lequesne index and 5 m timed up & go test were used to assess disability. Beck Depression Inventory was used to diagnose and measure the severity of depression. All subjects participated in a 10-session standard physical therapy program. After the physical therapy program, the subjects whose Beck Depression Inventory score were greater than 13 were consulted to the Psychiatry Department for the definitive diagnosis and treatment of depression. All subjects were contacted by telephone at 6 months after the physical therapy program. Forty-nine subjects who returned for the 6-month follow-up were re-assessed using the same measurements. Results: According to the Beck Depression Inventory, the patients in the depressed group had higher disability scores according to the Lequesne index when compared to the non-depressed group (p=0.009). Pain severity was also higher in the depressed group but the difference was not statistically significant (p=0.051). At the 6-month follow-up assessment, a statistically significant decrease in disability and pain was found in all subjects (p=0.000). Depression scores were also reduced in all subjects, but this was not statistically significant (p=0.052). Conclusion: A positive relation between pain, disability and depression was found in patients with knee osteoarthritis; however, given the small number of depressed patients in our study, further research is needed to support this relation and to examine the effects of depression treatment on pain and disability. (Turk J Rheumatol 2009; 24: 196-201)